Środki pieniężne - inwestycja czy...? - Rak, Aleksander (Cash Assests - Investment or...?, 2005)
The aim of the paper is proving that classifying cash assets to short-term investments (recommended by Polish Accounting Act) is at least questionable. As there is no doubt that these assets meet premises to classify them to current assets, we should consider classifying them to investments. Apart from few exceptions (as bank savings or foreign exchange kept in order to gain income on exchange rate differences) holding cash do not bring economic benefits - neither from asset's value increase, nor from interests. In fact possession of cash and bank accounts usually brings additional costs. This property makes cash assets similar to another element of current assets - inventory. The paper is trying to answer whether cash meets premises to classify them to inventory.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (2); 2005; nr 1059, s. 358-363